Utilization of Flipbooks for Reading Skills in Indonesian School Students Davao Philippines - Yunia Tiara Riski; Muhammad Nur Huda; Wahono Widodo; Dian Permatasari Kusuma Dayu (Universitas Negeri Surabaya, 2025)
This study explores the use of the Flipbook platform as an instructional medium to enhance reading skills among students at the Indonesian School of Davao, Philippines. The need for effective and engaging learning media is crucial, particularly for students with unique characteristics, such as learners of Bahasa Indonesia for Foreign Speakers (BIPA), participants in the Basic Indonesian Knowledge Course (KPDI), and those newly introduced to Bahasa Indonesia. The study employed a qualitative descriptive approach, focusing on understanding how Flipbook can support reading comprehension and language acquisition. Data were collected through observations, interviews, and document analysis to examine the learning process and its effectiveness. The findings reveal a series of structured steps for implementing Flipbook in Bahasa Indonesia instruction, highlighting its role in improving students’ engagement, comprehension, and overall reading proficiency. The study demonstrates that Flipbook facilitates interactive and visually enriched learning experiences, making language acquisition more accessible and enjoyable. The results contribute to the development of innovative teaching strategies within the BIPA program, KPDI, and Overseas Indonesian Schools (SILN). This study underscores the potential of digital learning media in fostering literacy and offers practical implications for educators seeking to enhance reading skills in Bahasa Indonesia instruction.